Monitoring of Yangtze River Discharge at Datong Hydrometric Station Using Acoustic Tomography Technology - Zhu, Ze-Nan; Zhu, Xiao-Hua; Zhang, Chuanzheng; Chen, Minmo; Zheng, Hua; Zhang, Zhensheng; Zhong, Jiwen; Wei, Lixin; Li, Qiang; Wang, Hua; Li, Shuming; Kaneko, Arata (Frontiers in Earth Science, 2021)
To continuously monitor the discharge of the Yangtze River, two coastal acoustic tomography (CAT) systems with synchronized transmission were deployed at the Datong hydrometric station of the Yangtze River from July 2018 to January 2021. To accurately estimate the discharge of the Yangtze River, the cross-sectional averaged flow velocity and area data were estimated by establishing two empirical relationships: one between the range-averaged flow velocity measured by acoustic Doppler current profiler (ADCP) and the reciprocal travel time difference measured by CAT, and the other between the ADCP-measured cross-sectional area and the water-surface elevation (stage). Compared with the discharges directly measured by ADCP, our estimation had the root mean square error of 946 m3/s, accounting for 2.5% of the mean discharge. The discharges varied from 10,981 to 81,807 m3/s over the 2.5-years observational period, with a mean of 30,708 m3/s. The annual mean discharge was 29,163 and 34,763 m3/s in 2019 and 2020, respectively. Our monitoring successfully covered two complete flood processes, with a peak discharge of 69,744 (July 17, 2019) and 81,807 m3/s (July 13, 2020). Our study provides an innovative method to achieve accuracy and real-time monitoring of river discharges even during extreme flood events.